Removal of Cu Ions from Aqueous Solutions by Carbon Nanotubes - Yan-Hui Li; Zhaokun Luan; Xu Xiao; Xiangwen Zhou; Cailu Xu; Dehai Wu; Bingqing Wei (Adsorption Science & Technology)
Carbon nanotubes (CNTs), a new crystalline form in the carbon family, have been shown to be an effective adsorbent for Cu 2+ ion removal from aqueous solution. After oxidation with nitric acid, the adsorption capacity of the oxidized CNTs towards Cu 2+ ions at a pH of 5.2 reached 27.6 mg/g, compared to a value of only 14.4 mg/g for the as-grown CNTs under the same circumstances. Increasing the pH to 5.4 led to 95% removal of Cu 2+ ions with the oxidized CNTs, whereas with the as-grown CNTs it was necessary to increase the pH to 8.6 to achieve the same extent of removal. The Cu 2+ ion adsorption capacity increased with increasing CNT dosage for the different initial Cu 2+ ion concentrations. The kinetic curve for adsorption of the Cu 2+ ions suggested that not only the outer surfaces but also inner cavities and inter-layers in the structures of the CNTs were responsible for the removal of the ion from aqueous solutions.